Assessing agri-environmental strategies to reduce pesticide concentrations in surface drinking water sources, Coastal Charente River basin, SW France - Odile Phelpin; Françoise Vernier; Kévin Petit; David Carayon (Ecological Indicators)
Most surface water bodies are deteriorating, resulting in health risks and environmental damage. This study aimed to assess the performance of the modeled agri-environmental transition scenarios for restoring freshwater quality within the protection perimeter of strategic surface water drinking water catchments. Realistic agri-environmental scenarios with combined agronomic orientations were tested using a well-calibrated ecohydrological model. Their performance was quantified based on pesticide concentration reductions in freshwater bodies, focusing on temporal and spatial variability, using non-parametric tests. Our results show that it is possible to differentiate cropping mitigation scenarios according to their ability to limit pesticide transfers, taking into account the most influential biogeochemical factors in the catchment, their agronomic orientation, and their progressive implementation. Our study is also applicable to other contexts.